Comparison of Masked and Unmasked Face Recognition Performance with Hand-Crafted Methods - Torbati, Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
Face recognition, a biometric technology, identifies people by their distinctive facial attributes. An image of a person's face must be compared to a library of other people's images to authenticate their identification. Face recognition systems may be used for identification, surveillance, and safety. Deep learning algorithms provide precise face recognition even under challenging conditions. Due to COVID-19 and masks, facial identification from unconstrained images is almost impossible. To avoid COVID-19, most people use masks outside. In many cases, typical facial recognition technology is useless. The majority of contemporary advanced face recognition methods are based on deep learning, which primarily relies on a huge number of training examples. Considering simply the eye and forehead regions of the face, however, masked face recognition may be investigated using hand-crafted approaches at a lower computing cost than using deep learning systems. In this thesis, handcrafted techniques are used to extract eye region and forehead characteristics from masked faces. We intend to construct a low-cost system for recognizing masked faces and compare its performance to that of face recognition systems that do not use masks. This study compares the performance of masked and unmasked face recognition systems. Experiments are undertaken on two publicly accessible datasets for masked face recognition: Masked Labeled Faces in the Wild (MLFW) and Cross-Age Labeled Faces in the Wild (CALFW). A comparison of the performance of the systems are provided in the thesis.

ÖZ: Biyometrik bir teknoloji olan yüz tanıma, insanları ayırt edici yüz özelliklerine göre tanımlar. Bir kişinin yüzünün görüntüsü, kimliğini doğrulamak için diğer kişilerin görüntülerinden oluşan bir veri kümesi ile karşılaştırılmalıdır. Yüz tanıma sistemleri tanımlama, gözetleme ve güvenlik için kullanılabilir. Derin öğrenme algoritmaları, zorlu koşullar altında bile hassas yüz tanıma sağlar. Kısıtlanmamış görüntülerden yüz tanıma, günümüzde COVID-19 salgını ve yüz maskelerinin yaygınlığı nedeniyle neredeyse zordur. Evlerinin dışında, neredeyse herkes COVID-19 virüsünün bulaşmasını başarılı bir şekilde sınırlamak için maske takmıştır. Bu, standart yüz tanıma teknolojilerini birçok durumda neredeyse değersiz hale getirmiştir. Çağdaş gelişmiş yüz tanıma yöntemlerinin çoğu, öncelikle çok sayıda eğitim örneğine bağlı derin öğrenmeye dayanmaktadır. Bununla birlikte, yüzün sadece göz ve alın bölgeleri düşünüldüğünde, derin öğrenme sistemlerinden daha düşük bir bilgi işlem maliyetiyle el yapımı yaklaşımlar kullanılarak araştırılabilir. Bu tezde, maskelenmiş yüzlerden göz bölgesi ve alın özelliklerini çıkarmak için el işi teknikler kullanılmıştır. Maskeli yüzleri tanımak için düşük maliyetli bir sistem kurmak ve performansını maske kullanmayan yüz tanıma sistemleriyle karşılaştırmak amaçlanmıştır. Bu çalışma böylece maskeli ve maskesiz yüz tanıma sistemlerinin performansını karşılaştırmaktadır. Maskeli yüz tanıma için halka açık iki veri kümesi üzerinde deneyler yapılmıştır: Vahşi Doğada Maskeli Etiketli Yüzler (MLFW) ve Vahşi Doğada Çapraz Yaş Etiketli Yüzler (CALFW). Tezin sonunda iki sistemin performansının bir karşılaştırması sağlanmıştır.
Master of Science in Computer Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2023. Supervisor: Prof. Dr. Önsen Toygar.
Keywords: Thesis Tez; Computer Engineering Department; Computer Pattern Recognition; Human face recognition (Computer science); Image processing--Pattern recognition systems; Masked face recognition; Unmasked face recognition; Hand-crafted methods